Novel orthogonal methods to uncover the complexity and diversity of nuclear architecture. (April 2021) - Tjalsma, Sjoerd JD; de Laat, Wouter
Abstract : Recent years have seen a vast expansion of knowledge on three-dimensional (3D) genome organization. The majority of studies on chromosome topology consists of pairwise interaction data of bulk populations of cells and therefore conceals heterogenic and more complex folding patterns. Here, we discuss novel methodologies to study the variation in genome topologies between different cells and techniques that allow analysis of complex, multi-way interactions. These technologies will aid the interpretation of genome-wide chromosome conformation data and provide strategies to further dissect the interplay between genome architecture and transcription regulation.